APPLICATION OF THE BINARY NUMBER SYSTEM IN BLOOD GROUP TYPE CHECKING BASED EMBEDDED SYSTEM - Ricki Ananda; Muhammad Amin; Parini Parini (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: The Indonesian Red Cross or abbreviated as PMI, is one of the organizations in Indonesia engaged in the humanitarian field. PMI has branches in all cities in Indonesia such as the red cross in Asahan district. Currently, the Asahan district red cross has a blood donation stock of ± 100/360 cc per bag. The purpose of designing a blood group type reader is to increase the certainty of blood types that are tested by experts or medical workers from PMI Asahan, according to the testing of the tool design. This study used a qualitative type of method, namely data taken in the form of data on the condition of the blood when rhesus fluid was given, so that the data will be calibrated with the test results so that the right test results can be decided. The results of testing the device design with blood and fluids, found that blood group A+ got an LDR value of 19.5 and 4 with a bina-ry condition of 101, while for blood group B+ got an LDR value of 19, 4 and 4 with a bi-nary condition of 011, blood group AB+ got a value LDR 19, 3 and 4 with binary condi-tion 111, blood type O+ found LDR values 19, 2 and 4 with binary condition 001. Mean-while for basic conditions, or not detecting blood type, LDR conditions 20, <=4, <=4 and binary value is 000. After testing, all results of testing the design of the tool are in full ac-cordance with the results of the conclusions of the PMI Asahan medical personnel about the type of blood group Keywords: binary; blood donation; blood type detector Abstrak: Palang Merah Indonesia atau disingkat PMI, merupakan salah satu organisasi di Indonesia yang bergerak dalam bidang kemanusiaan. PMI memiliki cabang di seluruh kota di Indonesia seperti palang merah di kabupaten asahan. Saat ini palang merah kabupaten asahan memiliki stok sumbangan darah ± 100/360 cc setiap kantong. Tujuan dirancang nya alat pembaca jenis golongan darah untuk menambah kepastian jenis darah yang diuji tenaga ahli atau medis PMI Asahan, sesuai dengan pengujian dari rancangan alat. Penelitian ini menggunakan jenis metode kualitatif, yaitu data yang diambil berupa data kondisi darah ketika dikasi cairan resus, sehingga data tersebut akan dikalibrasi dengan hasil pengujian sehingga memutuskan hasil pengujian tepat. Hasil pengujian rancangan alat dengan darah dan cairan,  mendapati bahwa untuk golongan darah A+ mendapati nilai LDR 19, 5 dan 4 dengan kondisi biner 101, sementara untuk golongan darah B+ mendapati nilai LDR 19, 4 dan 4 dengan kondisi biner 011, golongan darah AB+ mendapati nilai LDR 19, 3 dan 4 dengan kondisi biner 111, golongan darah O+ mendapati nilai LDR 19, 2 dan 4 dengan kondisi biner 001. Sementara untuk kondisi dasar, atau tidak mendeteksi golongan darah, kondisi LDR 20, <=4, <= 4 dan nilai biner 000. Setelah dilakukannya pengujian, maka disimpulkan seluruh hasil pengujian rancangan alat sepenuhnya sesuai dengan hasil kesimpulan tenaga medis PMI Asahan tentang jenis golongan darah. Kata kunci: biner; donor darah; pendeteksi golongan darah